The Effect of Service Quality, Price and Trust on Consumer Loyalty - Maharani, Intan Putri Dwi; Prawitasari, Dian; Anomsari, Ariati; Haziroh, Awanis Linati (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research explores the impact of service quality, price, and customer trust on customer loyalty at Alfamart H385-Supriyadi Semarang. The research method employed is descriptive and correlational, with the population consisting of repeat customers at Alfamart. A total of 80 respondents were selected as samples using a random sampling method, and data were collected using a closed-ended questionnaire. The results of the analysis indicate that service quality, price, and customer trust significantly affect customer loyalty at Alfamart. Both service quality and price show a positive and significant influence on customer loyalty, with regression coefficient values of 0.320 and 0.269, respectively. Additionally, customer trust also has a positive and significant influence, with a regression coefficient value of 0.429. Simultaneous analysis reveals that all three factors collectively influence customer loyalty significantly, with an R- square value of 75.4%. The conclusion drawn from this study is that Alfamart H385-Supriyadi Semarang needs to pay attention to and enhance service quality, price, and customer trust to strengthen customer loyalty. These steps can assist the company in retaining existing customers, attracting new ones, and overall improving customer satisfaction.